Theoretical Foundations of Students’ Problem-based Learning Technology in the Establishments of Higher Education - Maiia Karpushyna (Pedagogical Discourse, 2018)
In the article the peculiarities of problem-based learning as a technology are determined, its characteristics and potential in the educational process of the higher educational establishments are defined. Thus, problem-based learning is an approach to professional education that stresses the use of real-life problems as a stimulus for learning, which is considered contextually valid, in the sense that the problems are taken from professional practice. As a result, students acquire knowledge organized around these problems being involved with reality; learn social and communicative skills in genuine discourse, which explains the rationale behind their actions.The definition of the problem-based learning technology has been clarified. Problem-based learning technology is a learning process implementation procedure, determined by the problem situation, which defines accordingly the integrated ways of organizing problem-based teaching and problem-based learning at all stages of problem-solving as well as autonomous levels, the purpose of which is to master certain problem-solving methods at the level of skills and abilities of mental activity. It has been explored that the origin of the problem-based learning is obliged to the development of the theory of teaching methods, and its didactic characteristic reflects the structure and function of the evolving education methods. Therefore, the detailed arguments for revealing theoretical basis of the system of problem-solving methods have been advanced, including the principles on which they are founded. The following basic principles have been selected: goal-oriented, situation-based and problem-solving learning, binary approach, theory and practice relationship, consciousness and intelligibility, active engagement, autonomy, and emotionality.The theoretical foundations of the problem-based learning technology are revealed. Among those foundations there is a theory of thinking development patterns, theory of teaching and learning methods, problem situation, problem-based learning environment, subject-object-subject interaction between participants of the educational process, interdisciplinary education content.The most challenging aspects of the future research in this area will concern the study of ways to efficiently combine problem-solving methods and to organize the educational process by the «problem scenario».